Cuff inflations do not affect night-time blood pressure: comparison of 24 h ambulatory blood pressure measured by a cuff and a tonometric device in type 2 diabetes. Issue 6 (December 2015) - Petersen, Emilie H.; Theilade, Simone; Hansen, Tine W.; Lindhardt, Morten K.; Rossing, Peter
Abstract : Discomfort related to cuff inflation may bias 24 h ambulatory blood pressure (BP) measurements, especially during night-time. We accessed the impact of cuff inflations by comparing 24 h BP recorded with a cuff-less tonometric wrist device and an upper-arm oscillometric cuff device. Fifty-three participants with type 2 diabetes were assigned randomly to four 24-h BP recordings with a cuff (TM2430: visit 1 or 2, and 4) and a tonometric device (BPro: visit 1 or 2, 3, and 4). The mean 24 h systolic BP was significantly higher when measured with the cuff versus the tonometric device (141.6±14.6 vs. 128.3±14.6 mmHg, P ⩽0.01), as was nocturnal BP (6.7±5.3 vs. 10.3±7.6%, P =0.002). In conclusion, nocturnal BP decline was higher when measured with the cuff device, suggesting that cuff inflations did not increase night-time BP. Further evaluation of the tonometric device using the updated European Society of Hypertension International Protocol revision 2010 is recommended before applying it in daily clinical practice.